Efeito da microencapsulação de EPA e DHA e do uso de urucum na qualidade de linguiça de tilápia - Sousa, Diógenes Gomes de (2020)
The objective was to produce tilapia sausage enriched with EPA and DHA and evaluate the effect of microencapsulation of marine fish oil and the addition of annatto during storage under freezing. The ionic gelation technique was used for the microencapsulation of marine fish oil. Six different tilapia sausage formulations were prepared, through a 3x2 factorial design, with 3 oil inclusions (Control; free oil - OL and microencapsulated oil - OM) and two levels of annatto (0 and 0.05%). Microparticles were evaluated for their chemical composition and microencapsulation efficiency, while tilapia sausages were evaluated for chemical, physical, freshness and lipid oxidation immediately after processing and over 90 days of storage. The microparticle had a high moisture content (81.71%), caused by the ionic gelation technique. The values of carbohydrates (8.06%) can be attributed to the encapsulation material while the values of lipids (8.91%) in the particle are related to the addition of marine fish oil. All sausages met the standards established by legislation, with the exception of the moisture content, which was above 70% for all formulations, justified by the high moisture content present in freshwater fish. The wall material, established a lower shear strength in sausages, while the use of annatto acted as colorific. During the entire storage period, samples containing OM showed characteristics of fresh meat, with lower levels of N-BVT and pH, possibly related to the acidification of the encapsulating material. The annatto did not act in the first storage period, however, at 90 days of storage, a reduction (p <0.05%) was found in the formation of substances reactive to thiobarbituric acid (TBARS), which may be related to its bioactive properties, that act in the elimination of free radicals. Sausages containing OM stood out for presenting a higher (p <0.05) concentration of EPA (4.15%) and DHA (2.26%) after 90 days of storage, acting in the protection of these fatty acids and maintaining the lipid quality of the product. Therefore, the present study shows the efficiency of the microencapsulation technique in protecting fatty acids (EPA and DHA) against oxidative processes in tilapia sausages, and that the use of annatto powder can be an alternative in replacing synthetic dyes, in addition to acting as an antioxidant.